2022
DOI: 10.1038/s41598-022-23926-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of human polymerized hemoglobin on guinea pig resuscitation from hemorrhagic shock

Abstract: For the past thirty years, hemoglobin-based oxygen carriers (HBOCs) have been under development as a red blood cell substitute. Side-effects such as vasoconstriction, oxidative injury, and cardiac toxicity have prevented clinical approval of HBOCs. Recently, high molecular weight (MW) polymerized human hemoglobin (PolyhHb) has shown positive results in rats. Studies have demonstrated that high MW PolyhHb increased O2 delivery, with minimal effects on blood pressure, without vasoconstriction, and devoid of toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…To date, rodent models of hemorrhagic shock and acute trauma show that some PolyhHb solutions may be beneficial as O 2 -carrying therapeutics, as they are attractive alternatives when blood transfusion is not an option. Furthermore, these preclinical studies are strengthened by data showing polymerized Hb equivalence to fresh blood and superiority to stored blood, offering an intriguing proof of concept. ,, However, these experiments are performed using unfractionated, and thus polydisperse, PolyhHb and do not study a toxicology-based model of underlying disease designed to predict effectiveness but also safety. Our prior work in a 25% blood volume exchange transfusion guinea pig model evaluating size-bracketed PolyhHbs shows bracket-specific characteristics, such as the rates of oxidation, O 2 offloading, and clearance were associated with PolyhHb MW .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, rodent models of hemorrhagic shock and acute trauma show that some PolyhHb solutions may be beneficial as O 2 -carrying therapeutics, as they are attractive alternatives when blood transfusion is not an option. Furthermore, these preclinical studies are strengthened by data showing polymerized Hb equivalence to fresh blood and superiority to stored blood, offering an intriguing proof of concept. ,, However, these experiments are performed using unfractionated, and thus polydisperse, PolyhHb and do not study a toxicology-based model of underlying disease designed to predict effectiveness but also safety. Our prior work in a 25% blood volume exchange transfusion guinea pig model evaluating size-bracketed PolyhHbs shows bracket-specific characteristics, such as the rates of oxidation, O 2 offloading, and clearance were associated with PolyhHb MW .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that PolyhHb filtered between 500 kDa and 0.2 μm avoid the adverse effects seen in clinical trials and have shown a proof of concept as an effective resuscitative fluid in a guinea pig model of hemorrhagic shock. 25 Investigation into the effect of MW on pharmacokinetics, pharmacodynamics, and toxicity of PolyhHb fractionated into smaller MW brackets was performed in a guinea pig exchange transfusion model. This study identified the MW bracket between 500−750 kDa as being optimal as a long circulating material based on pharmacokinetic, hemodynamic, and cardiac conduction analyses, 26 thus warranting further investigation in a translational toxicology model.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] To address these challenges, strategies to increase the molecular diameter of the HBOC and limit free hemoglobin in circulation have become requirements in the design of modern HBOCs. These strategies include chemical cross-linking of hemoglobin, [22,23] polymerization of hemoglobins, [24][25][26] and encapsulation of hemoglobin in liposome and nano-and microparticle systems. [27,28] Liposome encapsulated hemoglobin's have demonstrated many of the desired design criteria for an alternative oxygen carrier, including an absence of blood group antigens and blood-borne pathogens, and a prolonged storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…18 To address these challenges, strategies to increase the molecular diameter of the HBOC and limit free hemoglobin in circulation have become requirements in the design of modern HBOCs. These strategies include chemical crosslinking of hemoglobin, 19,20 polymerization of hemoglobin and crosslinked hemoglobins, [21][22][23] and encapsulation of hemoglobin in liposome and nano-and microparticle systems. 24,25 Liposome encapsulated hemoglobins have demonstrated many of the desired design criteria for an alternative oxygen carrier, including absence of blood group antigens and blood-borne pathogens and a prolonged storage capacity.…”
Section: Introductionmentioning
confidence: 99%